EL HARAKAH : Ahkaamu (Duuna) Wa Dalaalatuha As-Siyaaqiyah - Abu Awwas Ibrahim Asy-syimsani (UIN Maulana Malik Ibrahim, 2016)
It appears from this research that 'doon' is a vague adverb, and it always stays as an adverb.